Preoperative albumin level is a marker of alveolar echinococcosis recurrence after hepatectomy - Joliat, Gaëtan-Romain (World J Gastroenterol, 2017)
AIM: To identify a preoperative blood marker predictive of alveolar echinococcosis (AE) recurrence after hepatectomy. METHODS: All consecutive patients who underwent operation for liver AE at the Lausanne University Hospital (CHUV) between January 1992 and December 2015 were included in this retrospective study. Preoperative laboratory values of leukocytes, mean corpuscular volume (MCV), red blood cell distribution width (RDW), thrombocytes, C-reactive protein (CRP) and albumin were collected and analyzed. Univariate and multivariate Cox regression analyses were performed to determine the risk factors for AE recurrence after liver resection. A receiver operating characteristic (ROC) curve was used to define the best discrimination threshold of the blood marker. Moreover, recurrence-free survival curves were calculated using the Kaplan-Meier method. RESULTS: The cohort included 68 adult patients (37 females) with median age of 61 years [interquartile range (IQR): 46-71]. Eight of the patients (12%) presented a recurrence over a median follow-up time of 76 mo (IQR: 34-128). Median time to recurrence was 10 mo (IQR: 6-11). Median preoperative leukocyte, MCV, RDW, thrombocyte and CRP levels were similar between recurrent and non-recurrent cases. Median preoperative albumin level was 43 g/L (IQR: 41-45) for non-recurrent cases and 36 g/L (IQR: 33-42) for recurrent cases (P = 0.005). The area under the ROC curve for preoperative albumin level to predict recurrence was 0.840 (95%CI: 0.642-1, P = 0.002). The cut-off albumin level value was 37.5 g/L for sensitivity of 94.5% and specificity of 75%. In multivariate analysis, preoperative albumin and surgical resection margins were independent predictors of AE recurrence (HR = 0.099, P = 0.007 and HR = 0.182, P = 0.045 respectively). CONCLUSION: Low preoperative albumin level was associated with AE recurrence in the present cohort. Thus, preoperative albumin may be a useful biomarker to guide follow-up.